Changes in Postprandial Glucose and Systolic Blood Pressure Following Mango Consumption in Individuals With Overweight/Obesity. (7th June 2021) - Horne, Justine; Garneau, Véronique; Kearney, Michèle; de Toro-Martín, Juan; Pilon, Geneviève; Couture, Patrick; Marette, André; Vohl, Marie-Claude; Couillard, Charles
Abstract: Objectives: Polyphenolic compounds are potent modulators of several pathways regulating inflammatory processes, lipid metabolism and glucose metabolism. This study aimed to explore the cardiometabolic health impacts of daily mango consumption ( Mangifera indica ) in individuals with overweight/obesity. Methods: Changes in the cardiometabolic profile variables including glucose tolerance as well as physical activity habits and dietary intakes were assessed in this single-arm clinical trial of 8 men and 19 women with overweight or obesity, who consumed 280 g/day of frozen mango for 8 consecutive weeks. Results: The intervention was not associated with significant changes in body weight, waist circumference or plasma lipid concentrations. We however noted that after consuming mangos for 8 weeks, participants showed a 3.5% reduction in systolic BP (−4.2 ± 5.8 mmHg, P  = 0.011) as well as a 10.5% reduction in 2-hour plasma glucose concentration after a 75-g oral glucose tolerance test (−0.58 ± 1.03 mmol/L, P  = 0.008). When taken separately, we found that women exhibited significant decreases in systolic (−4.6 ± 5.6 mmHg, P  = 0.0001) and diastolic BP (−2.6 ± 4.9 mmHg, P  = 0.0322) as well as a 12.4% reduction in 2-hour plasma glucose response to the 75-g oral glucose tolerance test (−0.67 ± 1.07 mmol/L, P  = 0.0134) in response to the mango consumption. Similar changes were noted in men [i.e., decreases in systolic (−3.2 ± 6.7 mmHg, P  = 0.2) and diastolic BP (−4.0 ± 5.4 mmHg, P  = 0.07) as well as of 2-hr plasma glucose concentrations (−0.35 ± 0.97, P  = 0.3)] although these failed to reach statistical significance. Conclusions: Our results suggest that regular mango consumption may have beneficial effects on blood pressure and glucose tolerance in individuals with overweight/obesity. Further studies need to be conducted to validate the metabolic relevance of our observations with regards to cardiometabolic health. Funding Sources: This project was funded by the National Mango Board. JRH received postdoctoral fellowships from CIHR, INAF and NUTRISS. M-CV holds a Tier 1 Canada Research Chair in Genomics Applied to Nutrition and Metabolic Health. AM is chairholder of the Pfizer Canada – CIHR Chair in the Pathogenesis of Insulin Resistance and Cardiovascular Diseases.